Designing and validating the Dubai Tool for Developmental Screening (DTDS) - Alolama, Fatma Mohammad; Mohammad, Haitham Mahmoud; Alhmid, Idris Helal; Alhammadi, Hanan Mohammed (Frontiers in Pediatrics, 2022)
Background: Early detection of developmental problems is vital for facilitating early access to targeted intervention and augmenting its beneficial outcomes. Standardized developmental screening tools are known to enhance detection rates of developmental problems compared to clinical judgement alone and are widely recommended to be used in infants and young children. Most of the available developmental screening tools have been developed in Western countries. Many of their items may not be suitable for other cultures and most of them are expensive. Currently, none of the developmental screening tools have been validated in the United Arab Emirates (UAE), and few are available in the Arabic language. Objective: To create and validate a developmental screening tool, in both English and Arabic, that is simple, quick to use, and culturally relevant to the United Arab Emirates (UAE) child population aged 9–48 months. Methods: The available literature was used to create a list of developmental milestones in five domains for children aged 9–48 months, divided into seven age groups. The selected milestones were used to create questionnaires in both English and Arabic, which were pilot tested twice. Each time, the results were analyzed and used to select, modify, and rephrase questions. Validation of the Dubai Tool for Developmental Screening (DTDS) was done against Parents’ Evaluation of Developmental Status (PEDS) as a gold standard instrument. The DTDS and PEDS were administered cross-sectionally to parents of 1400 children in seven age groups. Sensitivity, specificity, and kappa agreement of the DTDS compared with PEDS were calculated. Results: The DTDS had a sensitivity of 100% in four age groups and 75%–78% in the other three age groups. Specificity ranged from 96% to 99% across all age groups. The kappa measure showed substantial agreement in five age groups, a moderate agreement in one age group, and a fair agreement in one age group. Conclusions: The DTDS is a valid screening tool for early identification of developmental delays and disabilities in early childhood.